Household and occupational exposure to pesticides and risk of breast cancer - El-Zaemey, S.; Heyworth, J.; Glass, D.; Peters, S.; Fritschi, Lin (Taylor & Francis, 2014)
The association between breast cancer in women and the use of household or occupational pesticides was examined in a population-based case-control study. This study was conducted in Western Australia in 2009–2011and included 1,789 controls and 1,205 cases. Information on household pesticide exposure was collected from questionnaires. For occupational pesticide exposure, job-specific modules (JSMs) were used. To evaluate potential recall bias, we stratified the analysis by belief about whether pesticides contribute to breast cancer. Unconditional logistic regression wasused to calculate odds ratios (ORs) and 95% confidence intervals (CIs). Women’s exposures to pesticides in households and workplaces were not related to increased risk of breast cancer (OR = 1.10; CI: 0.86–1.37) and (OR = 0.77; CI: 0.45–1.32), respectively. The prevalence of occupational exposure to pesticides among women in our study was low. In the stratified analyses, the odd ratios associated with household pesticide use were similar among participants who believed pesticides increased breast cancer risk and those who did not. The results of our study did not showassociations between breast cancer and household or occupational exposure to pesticides.